Traumatic hemobilia in a seven-year-old girl - Taibo Canale, Walter (Cirugía del Uruguay, 2020)
The author presents a case of traumatic hemobilia in a seven-year-old girl, cured by cholecystostomy. The original trauma caused a brain coma and a associated rupture of the liver and spleen. Regarding this case, 15 published cases are reviewed.